TURKISH PRE-SERVICE EFL TEACHERS' PERCEPTIONS OF CREATIVITY - Gökçe Kurt; Okan Önalan (Informascope, 2018)
Creativity is considered one of the key 21st century skills and has received an increasing amount of attention in the field of education. How teachers perceive creativity has a significant impact on their pedagogical practices to stimulate student creativity in the classroom. The present exploratory study, based on a qualitative approach, aimed to investigate pre-service English teachers' perceptions of creativity. Analysis of data coming from a semi-structured focus-group interview with eight pre-service teachers revealed their perception of creativity as being different and unique, having extraordinary ideas and being able to produce original outcomes. The participants posited that creativity was innate to some extent and environmental factors such as family environment, cultural background and school education contributed to its development later in life. They suggested using open-ended, communicative, and collaborative tasks in English classrooms to foster student creativity. As prospective teachers, they perceived themselves creative to some extent, but felt unprepared to teach creativity. Finally, they all agreed on the facilitative role of teacher education in helping PTs teach creatively and develop an understanding of teaching creativity.